Leadership content and methods of the Hanoi Party Committee in building urban government - Tran Thi Phương Hoa (Journal of State Management, 2024)
Urbanization is progressing vigorously in Hanoi. The implementation of the urban government model and the formation of smart cities are leading to changes in the leadership content and methods of the Hanoi Party Committee in building urban government. Therefore, identifying the leadership content and techniques accurately for building urban government is the basis for assessing the current situation and proposing directions and solutions to enhance the Party Committee's leadership in building urban government.